Introduction: Climate Justice in the Anthropocene - Sam Adelman; Louis Kotzé (Oñati Socio-Legal Series, 2021)
The need to address climate and environmental change becomes ever more urgent as climate harms and ecological destruction intensify and become more frequent. The articles in this issue emerged from a workshop in 2019, and they explore the multi-faceted nature of climate justice against the backdrop of the Anthropocene trope. The articles address specific issues such as corporate responsibility, the plight of farmers in India, climate displacement, and gender justice. In doing so, they reveal common themes such as the limitations and failings of business as usual and law as usual, the centrality of human rights and vulnerability theory in the pursuit of climate justice, the indivisibility of justice, and alternatives ways of achieving it. La necesidad de ocuparnos del cambio climático y medioambiental está adquiriendo una urgencia creciente a medida que los daños climáticos y la destrucción ecológica se intensifican y se vuelven más frecuentes. Los artículos de este número se originan en un workshop de 2019, y exploran la naturaleza polifacética de la justicia climática en el escenario del tropo del Antropoceno. Los artículos se ocupan de temas concretos, como la responsabilidad empresarial, la lucha de los granjeros de India, el desplazamiento por motivos climáticos y la justicia de género. Así, revelan temas comunes, como son las limitaciones y fallos de las formas de siempre en los negocios y en el derecho, la centralidad de los derechos humanos y la teoría de la vulnerabilidad en la búsqueda de la justicia climática, la indivisibilidad de la justicia y maneras alternativas de conseguirla. Available from: https://doi.org/10.35295/osls.iisl/0000-0000-0000-1168